Davidson's principles and practice of medicine - Penman, Ian D.; Ralston, Stuart; Strachan, Mark W. J.; Hobson, Richard P. (London ; New York : Elsevier, 2023)
Well over two million medical students, doctors and other health professionals around the globe have owned a copy of Davidson's Principles and Practice of Medicine since it was first published over 70 years ago. Now in its 24th Edition, this thoroughly updated textbook describes the pathophysiology and clinical features of the most frequently encountered conditions in the major specialties of adult medicine, and explains how to recognise, investigate, diagnose and manage them. Taking its origins from Sir Stanley Davidson's much-admired lecture notes, Davidson's has endured because it keeps pace with how modern medicine is taught and provides a wealth of trusted information in an easy-to-read, concise and beautifully illustrated format.
1. Clinical decision-making / N Cooper and AL Cracknell -- 2. Clinical therapeutics and good prescribing / SRJ Maxwell -- 3. Clinical genetics / K Tatton-Brown -- 4. Clinical immunology / SL Johnston -- 5. Population health and epidemiology / H Campbell and DA McAllister -- 6. Principles of infectious disease / JAT Sandoe and DH Dockrell -- 7. Oncology / S Clive and M Stares -- 8. Pain and palliative care / LA Colvin and M Fallon -- 9. Acute medicine and critical illness / VR Tallentire and MJ MacMahon -- 10. Poisoning / SHL Thomas -- 11. Envenomation / J White -- 12. Medicine in austere environments / AC Baker -- 13. Infectious disease / DH Dockrell, S Sundar and BJ Angus -- 14. HIV infection and AIDS / G Maartens -- 15. Sexually transmitted infections / DJ Clutterbuck -- 16. Cardiology / DE Newby and NR Grubb -- 17. Respiratory medicine / IJ Clifton and DAB Ellames -- 18. Nephrology and urology / B Conway, PJ Phelan and GD Stewart -- 19. Clinical biochemistry and metabolic medicine / A Mather, DR Sullivan and E Miller-Hodges -- 20. Endocrinology / JDC Newell-Price and FW Gibb -- 21. Diabetes mellitus / JR Petrie and JG Boyle -- 22. Nutritional factors in disease / AG ShandShand and MEJ Lean -- 23. Gastroenterology / A Rej, TS Chew and DS Sanders -- 24. Hepatology / MJ Williams and TT Gordon-Walker -- 25. Haematology and transfusion medicine / HG Watson, DJ Culligan and LM Manson -- 26. Rheumatology and bone disease / GPR Clunie and SH Ralston -- 27. Dermatology / SH Ibbotson -- 28. Neurology / DPJ Hunt and MD Connor -- 29. Stroke medicine / W Whiteley and R Woodfield -- 30. Medical ophthalmology / JA Olson -- 31. Medical psychiatry / RM Steel and SM Lawrie -- 32. Maternal medicine / L Mackillop and FEM Neuberger -- 33. Adolescent and transition medicine / RJ Mann -- 34. Ageing and disease / TJ Quinn -- 35. Laboratory reference ranges / SJ Jenks.
Previous edition: 2018.
"70th anniversary edition"--Cover.
Includes bibliographical references and index.
Keywords: Medicine